A systematic review and meta‐analyses of regional perfusion in donation after circulatory death solid organ transplantation. (19th October 2021) - De Beule, Julie; Vandendriessche, Katrien; Pengel, Liset H. M.; Bellini, Maria Irene; Dark, John H.; Hessheimer, Amelia J.; Kimenai, Hendrikus J. A. N.; Knight, Simon R.; Neyrinck, Arne P.; Paredes, David; Watson, Christopher J. E.; Rega, Filip; et al.
Summary: In donation after circulatory death (DCD), (thoraco)abdominal regional perfusion (RP) restores circulation to a region of the body following death declaration. We systematically reviewed outcomes of solid organ transplantation after RP by searching PubMed, Embase, and Cochrane libraries. Eighty‐eight articles reporting on outcomes of liver, kidney, pancreas, heart, and lung transplants or donor/organ utilization were identified. Meta‐analyses were conducted when possible. Methodological quality was assessed using National Institutes of Health (NIH)‐scoring tools. Case reports (13/88), case series (44/88), retrospective cohort studies (35/88), retrospective matched cohort studies (5/88), and case‐control studies (2/88) were identified, with overall fair quality. As blood viscosity and rheology change below 20 °C, studies were grouped as hypothermic (HRP, ≤20 °C) or normothermic (NRP, >20 °C) regional perfusion. Data demonstrate that RP is a safe alternative to in situ cold preservation (ISP) in uncontrolled and controlled DCDs. The scarce HRP data are from before 2005. NRP appears to reduce post‐transplant complications, especially biliary complications in controlled DCD livers, compared with ISP. Comparisons for kidney and pancreas with ISP are needed but there is no evidence that NRP is detrimental. Additional data on NRP in thoracic organs are needed. Whether RP increases donor or organ utilization needs further research. Abstract : This systematic review and meta‐analyses summarizes all available evidence on regional perfusion in donation after circulatory death donors. It found that regional perfusion is feasible and safe and reduces some complications after transplantation of organs that underwent regional perfusion.